Effects of different cutting techniques on change of direction speed in team handball - Engel, P.; Seipp, D.; Klatt, S.; Fasold, F. (Kinesiology, 2025)
Change of direction (COD) actions play a crucial role in team handball performance. Achieving equal speed during specific cutting manoeuvres on the left and right side is believed to be advantageous for successful tactical behaviour. Although studies have investigated lateral disparities in movements towards and against the throwing arm, there is a lack of sport-specific evidence regarding the advantages and disadvantages of different cutting techniques in terms of direction and speed. This study aimed to explore the impact of technique on COD speed with the ball during team handball-specific cutting maneuvers. Change of direction speed was evaluated and compared under three conditions: (1) split-step technique, (2) side-step technique, and (3) individually preferred skill. A total of 19 male, active, injury-free team handball players (mean age 21.59 ± 2.60 years) with an average of 15.26 ± 4.33 years of team handball experience participated. Post-hoc video analysis was employed to calculate COD speed. No significant interaction between the direction of movement (towards or against the throwing arm) and technique was found (p=.09). However, a significant main effect of direction (p<.001) and technique (p=.013) was observed. Results indicated a higher COD speed when moving in the direction of the throwing arm. Additionally, a significant difference was found between individual skill and split-step technique (p=.01). Overall, the findings suggest that differences in COD speed, whether towards or against the throwing arm, are not attributable to movement technique.